2011
DOI: 10.1021/bm101185t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amphiphilic Star Block Copolymers and Their Evaluation as Transdermal Carriers

Abstract: Amphiphilic star polymers offer substantial promise for a range of drug delivery applications owing to their ability to encapsulate guest molecules. One appealing but under-explored application is transdermal drug delivery using star block copolymer reverse micelles as an alternative to the more common oral and intravenous routes. 6- and 12-arm amphiphilic star copolymers were prepared via atom transfer radical polymerization (ATRP) of sequential blocks of polar oligo (ethylene glycol)methacrylate and nonpolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 65 publications
3
35
0
Order By: Relevance
“…Star polymers' multiarm structure, globular shape, and multiplicity of end groups imparts on them a unique set of properties (e.g., crystalline, mechanical, and viscoelastic properties), when compared with their linear analogs. Perhaps most significantly, the three‐dimensional architecture of appropriately designed amphiphilic star polymers can be tailored to encapsulate guest molecules providing relatively rapid access to well‐defined nanocarriers for applications in drug delivery 2–4. There are three general strategies for the synthesis of star polymers, each of which exhibits particular advantages and disadvantages: the “core first” approach, the “arm first” approach, and the “graft onto” approach 5–8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Star polymers' multiarm structure, globular shape, and multiplicity of end groups imparts on them a unique set of properties (e.g., crystalline, mechanical, and viscoelastic properties), when compared with their linear analogs. Perhaps most significantly, the three‐dimensional architecture of appropriately designed amphiphilic star polymers can be tailored to encapsulate guest molecules providing relatively rapid access to well‐defined nanocarriers for applications in drug delivery 2–4. There are three general strategies for the synthesis of star polymers, each of which exhibits particular advantages and disadvantages: the “core first” approach, the “arm first” approach, and the “graft onto” approach 5–8.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these materials were not analyzed in sufficient detail to judge their purity with regards to missing arms. Because of the interest in star polymers for biomedical applications such as transdermal drug carriers,4, 33, 34 it is critical to develop synthetic, purification, and characterization methodologies, which can reproducibly yield “perfect” star polymers, those which exhibit the exact number of arms as were targeted in their synthesis. For these reasons, a detailed study of the coupling, purification, and characterization of star polymers was performed and described below.…”
Section: Introductionmentioning
confidence: 99%
“…Besides dendrimers, several other types of initiators have also been explored, including branched N-[2-(2-bromoisobutyryloxy)ethyl] maleimide (BiBEMI)/ styrene intermediate, [222] hyperbranched poly(glycerol) (PG), [223] multifunctional molecules with sulfonyl chloride moieties, [224] and microgel cores. [226][227][228] Thus, the biocompatibility of amphiphilic block copolymer arms is often of primary concern, [229][230][231] and much effort has been spent trying to understand the encapsulation-release properties of the unimolecular micelles in drug delivery. [226][227][228] Thus, the biocompatibility of amphiphilic block copolymer arms is often of primary concern, [229][230][231] and much effort has been spent trying to understand the encapsulation-release properties of the unimolecular micelles in drug delivery.…”
Section: Star-like Block Copolymer Unimolecular Micellesmentioning
confidence: 99%
“…Although polymer containing as few as three arms connected to a central point is architecturally defined as a star molecule, it is difficult to be used as unimolecular container unless the arms are bulky with dangling grafted side chains 42, 43. As the density of radiating arms decreases quickly with the radius from the core, star polymers with too few arms tend to have interpenetrated arms with each other, resulting in multimolecular aggregates in selective solvent 44, 45.…”
Section: Designing Principles For Core‐shell Structured Star Polymersmentioning
confidence: 99%
“…On the other hand, several reports indicated that star aggregation was the dominant product in their studies, rather than unimolecular containers. Grayson and co‐workers43 reported that star polymers containing 12 block copolymer arms of Core‐[POEGMA‐ b ‐poly(lauryl methacrylate)] 12 with star molecular weight $\overline{M}_{\rm n}$ ≈ 65 000 could not be dissolved as individual star molecule in squalane at a variety of concentrations (from 0.1 to 20 mg mL −1 ). Star aggregation was also reported for 8‐arm star block copolypeptides, containing poly(ethylene imine) core (PEI, $\overline{M}_{\rm n}$ = 1800), hydrophobic polyphenylalanine inner block (DP = 8), and negatively charged polyglutamate outer shell (DP = 16 and 32) (Core (PEI) ‐[(Phe) 8 ‐ b ‐(Glu) 16 ] 8 and Core (PEI) ‐[(Phe) 8 ‐ b ‐(Glu) 32 ] 8 ) 50.…”
Section: Designing Principles For Core‐shell Structured Star Polymersmentioning
confidence: 99%